ORIGIN AND CULTURAL MEANING OF CLASSICAL CHINESE MUSIC AND DANCE - Thuc, Nguyen Anh (VNU Journal of Foreign Studies; Vol 34 No 6DO - 10.25073/2525-2445/vnufs.4329, 2018)
Classical Chinese dance and music are an integral part of the course “An Introduction to Chinese Studies 2” for third-year students of the Faculty of Chinese Language and Culture,  University of Languages and International Studies, Vietnam National University, Hanoi. Therefore, in order to provide an overview and better understanding of Chinese history, people and culture in general as well as Chinese art in particular, this paper synthesizes and analyzes the relationship between classical Chinese music and dance through all Chinese dynasties. Accordingly, the great cultural value of classical Chinese dance and music will be highlighted.